Contemporary Developments in Child Protection Broadening Challenges in Child Protection - Nigel Parton (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2015)
Volume 3 "Broadening Challenges in Child Protection" takes a somewhat broader brief and reflects many of the changes over the past twenty five years in terms of the broadening of concerns from maltreatment within the family to maltreatment in a variety of extra-familial contexts, including: sport, the internet, various institutional settings and is much more concerned with sexual abuse and the challenges for criminal justice and public protection.